Risk Genetic Variants (IL-10) for Osteoporosis in Han Population from Northwest China - Rong K; Lang Y; Zhou Y; Ni L; Wang L; Wang L; Zhang Y; Wen F; Wang Z; Chen P (Dove Medical Press, 2023)
Kai Rong, Yi Lang, Yubo Zhou, Liangtao Ni, Lei Wang, Long Wang, Yaowu Zhang, Fengli Wen, Zhan Wang, Pingbo Chen Department of Traumatology, Traditional Chinese Medicine Hospital Affiliated to Xinjiang Medical University, Wulumuqi, Xinjiang, People's Republic of ChinaCorrespondence: Pingbo Chen, Department of Traumatology, Traditional Chinese Medicine Hospital Affiliated to Xinjiang Medical University, No. 116, Huanghe Street, Wulumuqi, Xinjiang, People's Republic of China, Tel/Fax +86-13899907800, Email xj.2016@foxmail.comBackground: Osteoporosis (OP) is a common metabolic bone disease characterized by loss of bone mass. IL-10 is considered to be a powerful immune and inflammatory suppressor. This study aimed to assess association between genetic loci in IL-10 and susceptibility to OP.Methods: Association analysis between IL-10 genetic loci and OP risk through SNPStats online software. FPRP analysis (false-positive report probability) verified whether the positive results were noteworthy findings. Linkage disequilibrium (LD) and haplotype analysis were completed by Haploview 4.2 and SNPStats. Multi-factor dimensionality reduction (MDR) was used to assess interaction of SNP-SNP in susceptibility to OP.Results: Allele "G" of IL-10-rs1554286 (OR = 1.21, p = 0.013), allele "C" of IL-10-rs1518111 (OR = 1.22, p = 0.011), allele "C" of IL-10-rs3024490 (OR = 1.20, p = 0.018), and allele "G" of IL-10-rs1800871 (OR = 1.21, p = 0.015) were risk factors for OP. In females, smoking, drinking, or aging ≤ 60 years old participants, the above genetic loci are also significantly associated with the increased risk of OP. FPRP analysis showed that all positive results are noteworthy findings. There are significant differences in serum levels of uric acid, mean hemoglobin concentration, or mean hemoglobin among different genotypes of IL-10 gene loci. MDR showed that four loci model composed rs1554286, rs1518111, rs3021094, and rs1800871 is the best model for predicting OP risk.Conclusion: IL-10-rs1554286, -rs1518111, -rs3021094, and -rs1800871 are risk factors for susceptibility to OP.Keywords: osteoporosis, IL-10, genetic loci, Han population from northwest China